Project Based Learning Model with Differentiated Learning Strategies on Learning Achievement of Elementary School Students - Sari, Auliya Ayu Fatichah; Fanny, Arif Mahya (PT. Pusmedia Group Indonesia, 2024)
This research is motivated by the learning process that is less than optimal for student learning achievement, this is due to the lack of learning models and strategies that are tailored to student learning needs. Teachers tend to use conventional learning models and lectures that make students bored faster and the learning needs of each student are not met optimally so that learning objectives do not reach the target. This research uses the Quasi Experimental method with a quantitative-based approach. The population in this study involved fourth grade students of SD Negeri Sedati Gede 2, and the sample of this study involved fourth grade students A with a total of 29 students and fourth grade students C with a total of 25 students. With the Posettest-only control research design used in two classes, namely the experimental class and the control class. Data collection methods/techniques in the form of test sheets with PJBL learning models with differentiated learning strategies that are applied through classroom learning such as the daily learning process. Based on the results of data analysis using SPSS version 25 with the Indipendent sample t test, it is known that the sig value. 0.000 <0.05 means that Ho is rejected and Ha is accepted. So it can be concluded that the application of the Project Based Learning learning model with differentiated learning strategies has a significant effect on the learning achievement of elementary school students.